Synthesis, Characterization and Preliminary Cytotoxic Study of Sinapic Acid and its Analogues - Yasser Fakri Mustafa (Journal of Global Pharma Technology, 2019)
The use of natural products to treat human diseases especially cancer is an interesting trend in pharmaceutical research. Sinapic acid, being a member of hydroxycinnamic acid family and having well-established pharmacological properties, could have a potential antitumor activity that has not been investigated sufficiently. This work aimed to test the preliminary cytotoxic effect of sinapic acid and nine of its synthesized analogues utilizing MTT assay on four cancer cell lines; which are: HeLa, AMN3, SKG, and MCF-7. The chemical structures of the intermediates and of the synthesized products were approving by analyzing their IR, 1H-NMR, 13C-NMR, and MS-ESI spectra. Results of the cytotoxicity study indicated that sinapic acid analogues 3a, 3c, 3d, 3e and 3h have lower IC50 values  than that of positive control on the tested cancer cell lines, while sinapic acid itself and the other synthesized analogues did not have such cytotoxic effect.Keywords: Sinapic acid, Analogues, Gastrodigenin, MTT, Cytotoxicity.